Opsonic activity of cerebrospinal fluid in experimental cryptococcal meningitis. - Hobbs, M M (1990)
The role of antibody in protection against infection with Cryptococcus neoformans is undefined. In this paper we describe the development of opsonic activity in the cerebrospinal fluid (CSF) of rabbits in response to cryptococcal meningitis. The opsonin appeared to be immunoglobulin G (IgG); the activity was heat stable, copurified with the IgG fraction during protein A separation, and could be absorbed by encapsulated cryptococci. Immunosuppression with cyclosporine could be administered to prevent or allow in vivo deposition of IgG on the polysaccharide capsule of yeast in the CSF. Both early and late cyclosporine regimens resulted in prolonged, severe meningeal infections corresponding to the complete absence of in vitro opsonic activity in the CSF. While the production of opsonic antibody is part of the successful host response against C. neoformans in the central nervous system of rabbits, the presence of specific immunoglobulin by itself is insufficient for complete protection.